Some aspects of biology of four species of rays off Mumbai water - Raje, Sadashiv Gopal (Indian Journal of Fisheries, 2011)
Females in Dasyatis sephen, D. uarnak and Gymnura micrura and males in Trygon walga are dominant in the fishery of rays. Females attain larger length than males. Breeding in D.sephen, T. walga and G. micrura occurs during a prolonged period. These species are demersal carnivores